KOMODIFIKASI KONTEN ASING DAN LOKAL OMETV PADA KANAL YOUTUBE - Maria Febiana; Mardani, Puri Bestari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pembangunan Nasional Veteran Jakarta, 2023)
This research reviews YouTube content creators who take advantage of interactions with foreigners on the OmeTV platform in Indonesia. Researchers focus on the production and distribution of foreign and local content through the phenomenon of casual conversation as a form of capitalization. Previous researchers had the limitation that social media studies were subject to commodification (Fuchs, 2014b, 2019). In this study, researchers consider that content creators play an important role in commodifying content because YouTube is a channel that facilitates the formation of popularity. This assumption is based on the argument that playlabor is voluntary while seeking pleasure in the social media space (Fuchs, 2014a). This text revived media production by linking it to cultural studies (Hesmondhalgh & Toynbee, 2008). This research aims to explain how content creators as well as OmeTV players commodify foreign and local content to gain economic benefits. Researchers used the method of content analysis and phenomenology. Content analysis aims to identify forms of content, while phenomenology is to explain the process of commodification and production relations between the OmeTV and YouTube platforms. The results of this study reveal that the commodification of foreign and local content with the seduction genre has become popular content that benefits YouTubers. In reproducing content, OmeTV players prepare verbal and nonverbal seduction communication strategies